Vídeo Síncrono com Preservação Digital e Registro Distribuído como um Serviço para Telessaúde - Sousa, Denio Mariz; Souza, Guido Lemos; Silva, Cícero I. da; Castro, Giuliano Maia (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
This paper proposes a video as a service (VaaS) platform enabling synchronous video and confidential transmission based in an open and scalable architecture in order to simplify the integration of streaming features in telehealth systems. The platform will provide participant authentication, preservation and recovery of videos with proof of existence, integrity and authenticity through digital certificates and blockchain registration, and the association of the recorded media with the patient's electronic medical record. The goal is that users and health professionals can adopt synchronous video resources to carry out the activities of supervision, teleconsulting, telediagnosis and preceptory of resident doctors with focus on Primary Health Care in remote locations in a safe and reliable way.